A Two-Dimensional Multiple-Choice Model Accounting for Omissions - Kreitchmann, Rodrigo Schames; Abad, Francisco José; Ponsoda, Vicente (Frontiers in Psychology, 2018)
This paper presents a new two-dimensional Multiple-Choice Model accounting for Omissions (MCMO). Based on Thissen and Steinberg multiple-choice models, the MCMO defines omitted responses as the result of the respondent not knowing the correct answer and deciding to omit rather than to guess given a latent propensity to omit. Firstly, using a Monte Carlo simulation, the accuracy of the parameters estimated from data with different sample sizes (500, 1000 and 2000 subjects), test lengths (20, 40 and 80 items) and percentages of omissions (5%, 10% and 15%) were investigated. Later, the appropriateness of the MCMO to the Trends in International Mathematics and Science Study (TIMSS) Advanced 2015 mathematics and physics multiple-choice items was analyzed and compared with the Holman and Glas’ Between-item Multi-dimensional IRT model (B-MIRT) and with the three-parameter logistic (3PL) model with omissions treated as incorrect responses. The results of the simulation study showed a good recovery of scale and position parameters. Pseudo-guessing parameters (d) were less accurate, but this inaccuracy did not seem to have an important effect on the estimation of abilities. The precision of the propensity to omit strongly depended on the ability values (the higher the ability, the worse the estimate of the propensity to omit). In the empirical study, the empirical reliability for ability estimates was high in both physics and mathematics. As in the simulation study, the estimates of the propensity to omit were less reliable and their precision varied with ability. Regarding the absolute item fit, the MCMO fitted the data better than the other models. Also, the MCMO offered significant increments in convergent validity between scores from multiple-choice and constructed-response items, with an increase of around 0.02 to 0.04 in R2 in comparison with the two other methods. Finally, the high correlation between the country means of the propensity to omit in mathematics and physics suggests that (1) the propensity to omit is somehow affected by the country of residence of the examinees, and (2) the propensity to omit is independent of the test contents.